Association of dog ownership and dog walking with human physical activity - Koichiro Oka; Ai Shibata; Kaori Ishii (Japanese Society of Physical Fitness and Sports Medicine, 2014)
There has been a growing interest in dog ownership and walking as a unique and potential resource to provide physical activity for many individuals in the community. The present study reviewed current trends regarding the studies on dog ownership, dog walking, and human health, and clarified the future direction of research on the topic. There is evidence to suggest that it is not dog ownership itself, but rather dog-walking that contributes to increased physical activity and the likelihood of meeting public health guidelines for physical activity. Also, a growing body of literature indicates that dogs appear to provide an important form of social support, motivation, and obligation that encourages dog owners to walk. Regarding the environmental and policy-related factors associated with dog walking, some literature showed that access to a dog-supportive park/area or living in a walkable neighborhood seems to positively affect dog owners walking with their dog. The evidence is still limited on interventions for promoting dog owners walking with their dog. With the high level of dog ownership in many industrialized countries, further evaluation of physical activity, including dog walking and use of an accelerometer, identification of factors related to dog owners' regular/irregular dog walking by means of a longitudinal study, and implementation of an intervention study related to the promotion of physical activity among dog owners with a focus on dog walking are needed.